(untitled) (Malaysian Journal of Applied Linguistics (MJoAL), 2024)
Learning English in Timor-Leste, a young country in the Expanding Circle of the world’s English usage, whose citizens speak multiple languages, poses diversified challenges that may be reduced through amendments to the educational curriculum in the country. Therefore, this article delved into the experiences of Timorese assistant teachers in a faith-based international school in Dili, Timor-Leste, as they acquire and use English. The lack of existing literature prompted the conduct of this qualitative case study, which involved a sample of eight assistant teachers. Four of the assistant teachers’ advisers were also interviewed for triangulation. Thematic analysis was used to analyse the data. The results showed that the participants had only been exposed to English from middle school, which resulted in their encountering various language challenges. These challenges included interacting with individuals with limited English proficiency, grappling with complex English terminology, and facing abrupt cognitive impediments. Notwithstanding these challenges, they exhibited coping strategies to surmount language barriers, including enrolling in English courses, seeking counsel from more knowledgeable individuals, engaging in informal English conversations, reading English literature, viewing English videos, and employing Google Translate. Moreover, they expressed their plans to engage in self-help practices and attend courses to improve their English language skills. Therefore, the study recommends refurbishing the country’s education policies through the inclusion of English subjects in the primary school curriculum and strengthening their undergraduate programmes on English language and literature.